The effect of major income sources on rural household food (in)security: Evidence from Swaziland and implications for policy. Issue 2 (3rd March 2016) - Mabuza, Majola L.; Ortmann, Gerald F.; Wale, Edilegnaw; Mutenje, Munyaradzi J.
ABSTRACT: The aim of this article was to investigate the food (in)security effect of household income generated from major economic activities in rural Swaziland. From a sample of 979 households, the results of a multinomial treatment regression model indicated that gender of household head, labor endowment, education, size of arable land, and location significantly influenced the households' choice of primary economic activity. Further results suggested that off-farm-income-dependent households were less likely to be food insecure when compared with on-farm-income-dependent households. However, on-farm-income-dependent households had a better food security status than their counterparts who depended on remittances and nonfarm economic activities.